Peningkatan Kompetensi Guru Melalui Pelatihan Penelitian Tindakan Kelas (PTK) Bagi Guru-Guru Akuntansi Se-SMA/SMK - Meinarni Asnawi; Pascalina Van Sweet Sesa (The Community Engagement Journal, 2021)
In order to improve teacher competence, PTK traning activities are carried out for high school teachers in Jayapura Regency and Jayapura City. Classroom Action Research (CAR) training activities using experimental methods using pretest and posttest design, the purpose of using this method is to ensure that this training can provide increased competence for partisicipants while participating in the training. The results of different tests showed that there was a significant difference in knowledge of 0,000 in the time before and aftar the provision of training materials. These results show that providing material stimulus about PTK can improve the competence of teachers in conducting classroom action research to achieve improved performance in teacher performance reporting. This activity aims to be able to foster scientific understanding and understanding of teachers about PTK, support teachers in writing PTK proposals, and teachers are expected to manage and analyze PTK results data, as well as be able to produce research reports and scientific publication.